Can we be certain that storage duration of transfused red blood cells does not affect patient outcomes?. (11th June 2019) - Trivella, Marialena; Stanworth, Simon J; Brunskill, Susan; Dutton, Peter; Altman, Douglas G
Abstract : Large pragmatic randomised trials have found no evidence that the age of red blood cells affects patient survival, but Trivella and colleagues say that problems with their design and analysis leave unanswered questions about safety